2019
DOI: 10.1097/rli.0000000000000560
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Multislice Echo Planar Imaging for Accelerated Diffusion-Weighted Imaging of Malignant and Benign Breast Lesions

Abstract: Objectives: Comparison of the diagnostic value of simultaneous multislice (SMS) accelerated diffusion-weighted echo planar imaging (EPI) of malignant and benign lesions of the breast compared with a reference EPI sequence. Materials and Methods: The study was approved by the institutional ethics committee. Sixty-eight patients were examined with a diffusion-weighted EPI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 60 publications
2
31
0
Order By: Relevance
“…The longer acquisition time of the rs‐EPI sequence compared to ss‐EPI was a major limitation for its use 11–13 . To overcome the longer scan time, the SMS acceleration technique, which has been used in the ss‐EPI sequence for breast MRI, can also be implemented in rs‐EPI sequences of breast MRI 15,16,18,28,29 . Filli et al 17 reported that the scan time was reduced from 4 minutes 21 seconds to 2 minutes 35 seconds with the implementation of two‐fold SMS acceleration to the rs‐EPI sequence, which was similar to our scan time reduction from 4 minutes 30 seconds to 2 minutes 31 sec.…”
Section: Discussionsupporting
confidence: 76%
“…The longer acquisition time of the rs‐EPI sequence compared to ss‐EPI was a major limitation for its use 11–13 . To overcome the longer scan time, the SMS acceleration technique, which has been used in the ss‐EPI sequence for breast MRI, can also be implemented in rs‐EPI sequences of breast MRI 15,16,18,28,29 . Filli et al 17 reported that the scan time was reduced from 4 minutes 21 seconds to 2 minutes 35 seconds with the implementation of two‐fold SMS acceleration to the rs‐EPI sequence, which was similar to our scan time reduction from 4 minutes 30 seconds to 2 minutes 31 sec.…”
Section: Discussionsupporting
confidence: 76%
“…Ohlmeyer et al and Frost et al both describe that SMS acquisitions do not introduce serious artifacts [24,25]. However, Filli et al describe an increase of shading in the prepectoral region and ghosting [26].…”
Section: Discussionmentioning
confidence: 99%
“…Another concern about multishot imaging is the increased scan time due to the increased number of shots. Multislice imaging, especially recently developed multiband multislice imaging, could help reduce the scan time of multishot imaging 35–37 . Navigator data that provides phase information for each shot may improve the performance of MUSE and shot‐LLR for a high number of shots.…”
Section: Discussionmentioning
confidence: 99%